156k views
1 vote
Solve the following:
1. 2(x+3)=x-4
2. 4(5x-2)=2(9x+3)
Please show working

User Jgg
by
5.2k points

2 Answers

7 votes

Answer:

1) x=-10

2)x=7

Explanation:

1.


2(x+3)=x-4\\\\2(x)+2(3)=x-4\\\\2x+6=x-4\\\\2x+6-x=-4\\\\x+6=-4\\\\x=-4-6\\\\x=-10\longleftarrow

2.


4(5x-2)=2(9x+3)\\\\4(5x)+4(-2)=2(9x+3)\\\\20x-8=2(9x+3)\\\\20x-8=2(9x)+2(3)\\\\20x-8=18x+6\\\\20x-8-18x=6\\\\2x-8=6\\\\2x=6+8\\\\2x=14\\\\x=7

User Miltonb
by
5.4k points
3 votes

Answer:

1. 2(x+3)=x-4 x=-10

2. 4(5x-2)=2(9x+3) x=7

Explanation:

1. 2(x+3)=x-4

2x+6=x-4

2x=x-10

x=-10

2. 4(5x-2)=2(9x+3)

20x-8=18x+6

20x=18x+14

2x=14

x=7

User Alternative
by
5.3k points